A Comparative Study on Outcome of Three Dissimilar Approaches for Supracondylar Humerus Fractures in Children - Muhammad Shahbaz Raza, Saeed Ahmad, Muhammad Sarfraz, Syed Alam Zeb, Rahim Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the radiological and functional results of lateral, medial and posterior access for K-wire fixation and open reduction among children with type III supracondylar fractures of the humerus. Study Design: A retrospective cohort study. Place and Duration: In the Orthopedic department of PIMS hospital, Islamabad for three-year duration from October 2018 to September 2021. Methods: All children with type-3 supracondylar fractures of the humerus who were operated and followed for at least one year who met the criteria of inclusion were involved in the research. There were 105 total children in this study. Lateral approach, Medial approach and posterior approach was used in 35 children each. Medical records were reviewed for surgical access, and children with lateral (LA), medial (MA), and posterior (PA) access were screened. The radiological result was evaluated by measuring the Baumann angle and Shaft Condylar Angle (SCA). All children were applied with Flynn’s criteria for functional results, which were classified as excellent, good, poor (unsatisfactory) and Fair (satisfactory). The results from medial, lateral and posterior approaches were compared and the P value was determined using the Kruskal-Wallis and Chi-square test (significant P value <0.05). Results: There were 105 total children in this study. Lateral approach, Medial approach and posterior approach was used in 35 children each. The mean age of children with Lateral approach was 8.60 ± 4.2 years, Medial approach 7.15 ± 4.1 years and with posterior approach 7.9 ± 5.9 years. The mean angle of the condylar axis was 41.9±7.4°, 42.5 ± 3.2 ° and 42.1±2.1 o in lateral approach, Medial approach and posterior approach respectively (p> 0.05). The mean Bauman angle was 20.1±3.9 o, 21.1±6.1 o and 22.2±3.4 o in lateral approach, Medial approach and posterior approach (P> 0.05). Excellent results were obtained in 25 (71.4%), 19 (54.3%) and 17 (48.6%) patients in lateral approach, Medial approach and posterior approach respectively. (P> 0.05) Good results were obtained in 10 (28.6%) children in LA, 16 (45.7%) children in MA and 18 (51.4%) children in PA (P> 0.05). Conclusions: The lateral approach for the supracondylar fracture gave better functional and radiological results in our patients in comparison to the medial and posterior approach. Though, the difference was not statistically significant.